Cover Image, Volume 37, Issue 2. Issue 2 (17th December 2015) - Unknown
Abstract : Napthalene diimides exhibit interesting photophysical properties that make them ideal targets as antenna molecules for dye‐sensetized solar cells. On page 304 (DOI:10.1002/jcc.24197 ), Joshua R. Mulder, Célia Fonseca Guerra, J. Chris Slootweg, Koop Lammertsma, and F. Matthias Bickelhaupt show, through TD‐DFT explorations and Kohn‐Sham MO analyses, how the S0 –S1 transition can be tuned and even pushed beyond the "700 nm barrier". Overcoming this barrier is crucial for developing photovoltaic devices that make use of the hitherto wasted near‐infrared photons in the solar spectrum. The cover illustration, designed by Jeroen Rombouts, was inspired by key orbitals involved in the tuning of the S0 –S1 transition.